21st Century Surface Science - A Handbook 2020
DOI: 10.5772/intechopen.92967
|View full text |Cite
|
Sign up to set email alerts
|

Smart Coatings with Carbon Nanoparticles

Abstract: Smart coatings based on polymer matrix doped with carbon nanoparticles, such as carbon nanotubes or graphene, are being widely studied. The addition of carbon nanofillers into organic coatings usually enhances their performance, increasing their barrier properties, corrosion resistance, hardness, and wear strength. Moreover, the developed composites provide a new generation of protective organic coatings, being able to intelligently respond to damage or external stimuli. Carbon nanoparticles induce new functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The first result was expected, since it has been reported that MWCNTbased strain sensors have generally limited sensitivity. 13,66,67 Sensitivity is much higher in low density network since fewer parallel conduction pathways contribute to the electrical conductivity. 64 In this work, the MWCNT network at 1% wt loading is quite dense; therefore, the applied strain does not greatly affect the CNT-to-CNT pathways resulting in low sensitivity.…”
Section: Strain Sensing Resultsmentioning
confidence: 99%
“…The first result was expected, since it has been reported that MWCNTbased strain sensors have generally limited sensitivity. 13,66,67 Sensitivity is much higher in low density network since fewer parallel conduction pathways contribute to the electrical conductivity. 64 In this work, the MWCNT network at 1% wt loading is quite dense; therefore, the applied strain does not greatly affect the CNT-to-CNT pathways resulting in low sensitivity.…”
Section: Strain Sensing Resultsmentioning
confidence: 99%
“…Carbon nanomaterials have exceptional mechanical, electrical and thermal properties, as well as high chemical stability, making them quite promising for protecting against corrosion in space [60]. Moreover, carbon nanomaterials can be incorporated into various matrix materials which can then be applied to metal surfaces as a coating, providing a protective barrier preventing the attachment of corrosive species [61]. The ability of carbon nanomaterials to improve the adhesion and durability of protective coatings is another factor that makes them promising for space applications where long-term performance and reliability are critical [62].…”
Section: Importance Of Carbon Nanomaterials For the Corrosion Mitigationmentioning
confidence: 99%
“…Smart coatings based on the polymer matrix doped with carbon nanomaterials, such as carbon nanotubes or graphene, enhance their performance, increasing their barrier properties, corrosion resistance, hardness, and wear strength [151][152][153][154][155]. This is a new generation of protective organic coatings, capable to respond intelligently to damage or external stimuli.…”
Section: Nanofabrication Aspects Of Green Procedures In Enhancing Coatings Multifunctionality (Green Corrosion Inhibitors Biomimetic Coatmentioning
confidence: 99%